PELATIHAN MEMBUAT PARFUM UNTUK MENINGKATKAN JIWA KEWIRAUSAHAAN SISWA DI SMP NEGERI 16 JAKARTA - Anwar, Saiful; Fitriani, Tria; Maulina, Trisia Loli; Anggraeni, Wulan; Herlina, Yena; Yuningsih, Yulia (Yayasan Education and Social Center, 2024)
Education is an agent of change, one of which can be done is by honing the entrepreneurial spirit of students. Entrepreneurship refers to a new creative result created by someone and carried out personally and the ability to see a situation in which there are various opportunities to gain profit, or obtain a solution in facing various obstacles/problems by prioritizing courage, sincerity, and all the abilities they have to create something new., until now the quality of education is still far from expectations. Education in Indonesia still only applies theoretical matters, but does not apply them in social life and is able to solve various problems they face every day. The right education to be applied in Indonesia is education that is oriented towards an entrepreneurial spirit, namely a spirit that is brave and able to face problems and find solutions on its own without relying on others. This is less noticed by schools in general, so that the entrepreneurial spirit embedded in students is not accommodated by schools, training is needed to improve students' entrepreneurial creativity